2019
DOI: 10.1007/s11060-019-03177-0
|View full text |Cite
|
Sign up to set email alerts
|

Spinal location is prognostic of survival for solitary-fibrous tumor/hemangiopericytoma of the central nervous system

Abstract: Background: Prior studies have highlighted infratentorial tumor location as a prognostic factor for solitary fibrous tumor (SFT) and hemangiopericytoma (HPC) of the central nervous system (CNS), and spinal location is considered a positive prognostic factor for other tumors of the CNS. While SFT/HPC of the CNS is known to frequently arise from the spinal meninges, there are no case series that report outcomes for spinally located CNS tumors, and their prognosis in relation to intracranial and other CNS-located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…The patients' ages ranged from 29 to 68 years, with most of them being middleaged. 22 In our study, the lesions were mainly distributed in the cervical (n = 12) and thoracic segments (n = 9), which is consistent with previous results. 9,12,23 Ki-67/MIB-1, an indicator of tumor proliferation, 24 was significantly higher in grade 3 tumors than in grade 2 tumors in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The patients' ages ranged from 29 to 68 years, with most of them being middleaged. 22 In our study, the lesions were mainly distributed in the cervical (n = 12) and thoracic segments (n = 9), which is consistent with previous results. 9,12,23 Ki-67/MIB-1, an indicator of tumor proliferation, 24 was significantly higher in grade 3 tumors than in grade 2 tumors in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained in our study, and no significant difference in sex distribution was found when comparing grade 2 and 3 SFTs. The patients' ages ranged from 29 to 68 years, with most of them being middle-aged 22 . In our study, the lesions were mainly distributed in the cervical (n = 12) and thoracic segments (n = 9), which is consistent with previous results 9,12,23 .…”
Section: Discussionsupporting
confidence: 92%
“…Informed consent was not necessary as no identifiable data was accessed. Data were collected and analyzed as described in previous reports (19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Data Sourcementioning
confidence: 99%
“…Several previous studies explored the prognostic factors of intracranial SFT/HPC, which mostly underlined the extent of resection (EOR) as a major factor for tumor recurrence and metastasis [ 9 16 ]. Other factors, including WHO classification [ 9 , 15 ], adjuvant therapy [ 16 20 ], age [ 21 , 22 ], location, and size of tumor [ 23 ] had also been reported that related to patient’s progression-free survival (PFS) and overall survival (OS). However, due to the rarity of intracranial SFT/HPC, little is known about the optimal treatment and prognostic factors, and our current knowledge about SFT/HPC is mainly derived from small case series [ 4 , 9 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%